Multidisciplinary Management of Prostate Cancer The Role of the Prostate Cancer Unit - Gentile, Vincenzo.; Gentile, Vincenzo.; Panebianco, Valeria.; Panebianco, Valeria.; Sciarra, Alessandro.; Sciarra, Alessandro. (Springer International Publishing : Imprint: Springer, 2014)
Prostate cancer is the most common neoplasm in men and its management is very complex, in terms of both diagnosis and treatment. In recent years the value of multidisciplinary management within a prostate cancer unit has been increasingly recognized. Such a multidisciplinary approach within a specialized unit involves a variety of specialists, including urologists, oncologists, radiotherapists, radiologists and pathologists. This book describes in detail the advantages of multidisciplinary management of prostate cancer. It opens by explaining the nature of the required multidisciplinary team and the potential benefits of the prostate cancer unit as a structure for the delivery of specialist multidisciplinary care. Epidemiological aspects favoring multidisciplinary management are described and each element of care within the context of the prostate cancer unit is then discussed; also has been described the role of advanced imaging (Multiparametric MRI) in the management of PCa. Early diagnosis, risk classification, treatment decision making, surgery, radiotherapy, medical therapies and health care support are all fully considered. This book will be informative and enlightening for all who are involved in the management of patients with prostate cancer.